2014
DOI: 10.2147/dddt.s52428
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pharmacodynamics of new oral drugs used in the treatment of multiple sclerosis

Abstract: New oral drugs have considerably enriched the therapeutic armamentarium for the treatment of multiple sclerosis. This review focuses on the molecular pharmacodynamics of fingolimod, dimethyl fumarate (BG-12), laquinimod, and teriflunomide. We specifically comment on the action of these drugs at three levels: 1) the regulation of the immune system; 2) the permeability of the blood–brain barrier; and 3) the central nervous system. Fingolimod phosphate (the active metabolite of fingolimod) has a unique mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 116 publications
(161 reference statements)
2
1
0
Order By: Relevance
“…These studies in conjunction with this study indicate that clozapine may help promote CNS repair and inflammatory damage. Moreover, orally-administered compounds that can cross the blood brain barrier such as clozapine may offer better access to the central nervous system than currently available protein or antibody-based treatments (di Nuzzo, Orlando, Nasca, & Nicoletti, 2014). The data presented in this thesis supports the possibility that clozapine is neuroprotective in ways that are also independent of the immune response.…”
Section: Discussionsupporting
confidence: 55%
“…These studies in conjunction with this study indicate that clozapine may help promote CNS repair and inflammatory damage. Moreover, orally-administered compounds that can cross the blood brain barrier such as clozapine may offer better access to the central nervous system than currently available protein or antibody-based treatments (di Nuzzo, Orlando, Nasca, & Nicoletti, 2014). The data presented in this thesis supports the possibility that clozapine is neuroprotective in ways that are also independent of the immune response.…”
Section: Discussionsupporting
confidence: 55%
“…These studies in conjunction with this study indicate that clozapine may help promote CNS repair and inflammatory damage. Moreover, orally-administered compounds that can cross the blood brain barrier such as clozapine may offer better access to the central nervous system than currently available protein or antibody-based treatments (di Nuzzo, Orlando, Nasca, & Nicoletti, 2014). The data presented in this thesis supports the possibility that clozapine is neuroprotective in ways that are also independent of the immune response.…”
Section: Discussionsupporting
confidence: 55%
“…Underlying mechanisms how Teriflunomide inhibited aggregation and decreased aggregate size of polyQ aggregates in this study are not clear, but the authors suggested that Teriflunomide prevented the incorporation of new polyQ into existing aggregates rather than disintegrating already formed aggregates. There have been multiple potential additional effects of Leflunomide/Teriflunomide, such as an inhibition of protein tyrosine kinases [ 78 , 79 ] resulting in decreased IgG1 secretion of stimulated B cells via a reduction of JAK3 and STAT6, or an inhibition of the mitogen-activated protein kinase (MAPK) and nuclear factor-kappa B (NF-κB) pathways [ 80 , 81 ], an inhibition of cyclooxygenase-2 [ 82 ], interference with the kynurenine pathway [ 83 ], and decreased T cell receptor (TCR)/CD3-mediated calcium mobilization during formation of the immunological synapse [ 84 ]. However, all these effects were observed in vitro at much higher concentrations than those required to block DHODH.…”
Section: Mode Of Actionmentioning
confidence: 99%